2016
DOI: 10.3109/14767058.2016.1144744
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress-induced Gadd45α inhibits trophoblast invasion and increases sFlt1/sEng secretions via p38 MAPK involving in the pathology of pre-eclampsia

Abstract: Oxidative stress-induced overexpression of Gadd45α might influence the activity of MMPs through activation of p38 MAPK signaling to affect the invasion of trophoblast cells, and increase the secretions of sFlt-1/sEng, which then participate in the pathogenesis of pre-eclampsia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 47 publications
1
25
0
Order By: Relevance
“…Our results demonstrated that p38 MAPK was upregulated by knockdown of HPSE, and when pretreated with BMS582949, SB203580, or BIRB796, the invasiveness of HTR8/SVneo cells with knockdown of HPSE was recovered. This revealed that the underlying mechanism by which knockdown of HPSE suppressed HTR8/SVneo cell invasion was by activating the p38 MAPK pathway, which was consistent with a previous report [ 25 ]. Proper phosphorylated p38 is necessary for the normal physiological function of the cells.…”
Section: Discussionsupporting
confidence: 92%
“…Our results demonstrated that p38 MAPK was upregulated by knockdown of HPSE, and when pretreated with BMS582949, SB203580, or BIRB796, the invasiveness of HTR8/SVneo cells with knockdown of HPSE was recovered. This revealed that the underlying mechanism by which knockdown of HPSE suppressed HTR8/SVneo cell invasion was by activating the p38 MAPK pathway, which was consistent with a previous report [ 25 ]. Proper phosphorylated p38 is necessary for the normal physiological function of the cells.…”
Section: Discussionsupporting
confidence: 92%
“…Gadd45α(DNA damage-inducible 45 alpha) is an oxidative stress-induced factor with high levels in PE. Gadd45αinhibits trophoblast invasion and regulates anti-angiogenesis factor secretion via the p38 MAPK signalling pathway[ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, concentrations of the antiangiogenic factors soluble fms-like tyrosine kinase-1 (sFLT-1) e15a and soluble endoglin were increased in the placenta as well as in the circulation of PE patients [109][110][111].…”
Section: Immunological Backgroundmentioning
confidence: 99%